Exposure assessment and process sensitivity analysis of the contamination of campylobacter in poultry products - Osiriphun,S. (Poultry Science Association, 2015)
Studies were conducted in a Thai poultry plant to identify the factors that affected numbers of Campylobacter jejuni in chicken carcasses. The concentrations of Campylobacter were determined using the SimPlate most probable number and modified charcoal cefoperazone deoxycholate plating methods. Results indicated that the mean concentrations of C. jejuni in carcasses after scalding, plucking, and chilling were 2.93 ± 0.31, 2.98 ± 0.38, 2.88 ± 0.31, and 0.85 ± 0.95 log cfu, whereas the concentrations of C. jejuni in the scalding tank water, plucked feathers, and chicken breast portion were 1.39 ± 0.70, 3.28 ± 0.52, and 0.50 ± 1.22 log cfu, respectively. Sensitivity analysis using tornado order correlation analysis showed that risk parameters affecting the contamination of C. jejuni in the chicken slaughter and processing plant could be ranked as chilling water pH, number of pathogens in the scald tank water, scalding water temperature, number of C. jejuni on plucked feathers, and residual chlorine in the chill water, respectively. The exposure assessment and analysis of process parameters indicated that some of the current critical control points were not effective. The suggested interventions included preventing fecal contamination during transportation; increasing the scalding temperature, giving the scalding water a higher countercurrent flow rate; reducing contamination of feathers in the scalding tank to decrease C. jejuni in the scalding water; spraying water to reduce contamination at the plucking step; monitoring and maintaining the chill water pH at 6.0 to 6.5; and increasing the residual chlorine in the chill water. These interventions were recommended for inclusion in the hazard analysis and critical control point plan of the plant. © 2011 Poultry Science Association Inc.